Online measurement of 1, 2, 4-trichlorobenzene as dioxin indicator on multi-walled carbon nanotubes. (1st January 2021) - Mubeen, Ishrat; Tulaphol, Sattrawut; Shengyong, Lu; Pan, Denggao; Zhang, Pengfei; Khan, Muhammad Sajid; Yan, Mi; Stevens, William R.
Abstract: Polychlorinated dibenzo-p-dioxin and dibenzofuran (PCDD/F) emission is one of main concerns for the secondary pollution of municipal solid waste incinerators (MSWI). For timely response to emission, 1, 2, 4-trichlorobenzene (1, 2, 4-TrClBz) as dioxin indicator can be monitored via online measurement techniques. In this study, multi-walled carbon nanotubes (MWCNTs) were investigated for their suitability as a 1, 2, 4-TrClBz sorbent for MSWI stack gas analysis. The tests include, batch adsorption, continuous adsorption-desorption of 1, 2, 4-TrClBz via thermal desorption coupled with gas chromatography (TD-GC-ECD), temperature and concentration stability of MWCNTs, and adsorption performance of the system. Thermogravimetric/derivative thermogravimetric (TGA/DTG) analysis reveals that MWCNTs has higher capacity in terms of weight loss (14.34%) to adsorb 1, 2, 4-TrClBz compared to Tenax TA (9.46%) and also shows fast desorption of adsorbate at temperature of 87 °C compared to Tenax TA (130 °C). Interestingly, carbon nanotubes and Tenax TA gave almost similar adsorption-desorption response, and from TD-GC-ECD analysis it was found that with increasing mass flow of 1, 2, 4-TrClBz (7.42 × 10 −6 - 44.52 × 10 −6  mg ml −1 ) through sorbent traps, average peak areas increased from 2.86 ± 0.02 to 13.54 ± 0.26 for MWCNTs and 2.89 ± 0.02 to 13.38 ± 0.12 for Tenax TA, respectively. The stability of MWCNTs for temperature was 400 °C and for concentration of 1, 2, 4-TrClBz was 50 ppbv. However, regeneration of sorbent at 100 ppbv (1, 2, 4-TrClBz) was not possible. TD-GC-ECD system showed high adsorption performance with 3.86% and 3.59% relative standard deviation at 250 °C and 300 °C, respectively. Further Fourier Transform Infrared Spectroscopy (FTIR) analysis confirmed that adsorbate can be fully desorbed at 300 °C. Graphical abstract: Image 1 Highlights: MWCNTs exhibited higher adsorption capacity for 1, 2, 4-TrClBz as compared to Tenax TA. A fast desorption of 1, 2, 4-TrClBz from CNTs was also observed. 1, 2, 4-TrClBz was fully desorbed at selected desorption temperature (300 °C) from CNTs. CNTs showed stability for tested desorption temperature and concentration of adsorbate. Abstract : MWCNTs exhibited higher adsorption capacity and fast desorption as a sorbent of 1, 2, 4-TrClBz compared to Tenax TA, for online measurement of dioxins from MSWI.